2015
DOI: 10.4141/cjas-2015-046
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spring versus summer calving on beef cattle economic performance in western Canada

Abstract: . 2015. The effects of spring versus summer calving on beef cattle economic performance in western Canada. Can. J. Anim. Sci. 95: 475Á486. The choice of calving date influences the net revenue of a calving operation as it affects the number of days that calves spend in each feeding phase and when they are subsequently marketed. These two factors determine the costs, revenue, and risk (variance) of each calving system for the calving phase of a beef system. The majority of cowÁcalf producers in western Canada h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Similar stochastic variables have been used in previous beef studies [28,58,59,60,61,62]. Khakbazan et al [30,31] reported a similar SERF analytical technique for ranking different beef management systems. Figure 2 presents the SERF approach using a negative exponential utility function.…”
Section: Co2 Equivalent Ch4 Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar stochastic variables have been used in previous beef studies [28,58,59,60,61,62]. Khakbazan et al [30,31] reported a similar SERF analytical technique for ranking different beef management systems. Figure 2 presents the SERF approach using a negative exponential utility function.…”
Section: Co2 Equivalent Ch4 Emissionsmentioning
confidence: 99%
“…The objective of this study was to evaluate the economic effects of barley or triticale silage-based diets and cattle e ciency type for backgrounding steers. Additionally, stochastic simulation, which allows cost, revenue, and production factors to be analyzed as statistical distributions rather than as point estimates [28,29,30,31] was used to assess probable cattle producer preferences. Finally, performance of animals in terms of CH 4 emissions (in CO 2 equivalent (CO 2 e)) under different diet treatments and cattle e ciency types was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The primary source of income for a cow-calf operation is generated through the sale of calves at weaning. This income is dependent on individual calf size; consequently, it is economically beneficial for all calves to have reached their maximum potential weight at an early age (Khakbazan et al 2015;Sheppard et al 2015). Calves who have experienced slower growth prior to weaning will either bring a lower price at weaning or will require the producer to further invest in their feeding and care to allow them to reach a higher BW over a longer period.…”
Section: Dam Nutritionmentioning
confidence: 99%
“…For instance, in some cases, groups on nonrested treatments might have a shorter grazing season than those on rested treatments. Therefore, bale grazing costs of $1-$2 head -1 d -1 (Table 4 in Khakbazan et al 2015) were added to all treatments that could no longer graze perennial residue or swathed annuals. Additionally, barley feed costs were added to account for cow weight deficiencies among treatments that would have to be regained over the winter.…”
Section: Production Costsmentioning
confidence: 99%
“…More recent agricultural studies using stochastic simulation in the analysis of net returns look at economic performance of different crop production systems (McLellan 2009;Barham et al 2011;Williams et al 2012) and livestock calving and finishing systems (Anderson et al 2004;Khakbazan et al 2014Khakbazan et al , 2015. The benefit of stochastic simulation models, in analyses comparing alternative systems, is that they allow uncertainty to be incorporated into the model through consideration of both various scenarios, as well as how scenario assumptions affect the expected values and variances of outcomes for key model variables.…”
Section: Introductionmentioning
confidence: 99%